Archi-Arché Tentoonstellingen. - Kenis, Jan (Tongeren : Provinciaal Gallo-Romeins Museum, 1993)
Garcet, Robert ; Herbecq, Bernard ; Hebbelinck, Pierre ; Delbroek, Jos ; van Lierde, Jan ; Neikes, Dieter ; Deleu, Luc ; Kieckens, Christian ; Pellens, Lucas ; Custers, Stefan ; Arets, Wiel ; Lemmen, Hans ; De Gregorio, Alfredo ; Daems, Walter ; Beel, Stephane ; Selinger, Patrick
Archi-Arché Tentoonstellingen, Provinciaal Gallo-Romeins Museum, Tongeren, zomer 1993
Nederlands
kunstcatalogus